Synthesis of three-dimensional boron carbon nitride foam - Choong, Wei Seng (2017)
In all sports, athletes are always training hard to break records. Apart from individual’s effort, technology and equipment are other factors that will affect performance. This project will be focusing on the synthesis of a better material to use as midsole for boosting running performance for athletes, yet still providing the comfort and protection that they need. Boron Nitride (BN) and Boron Carbon Nitride (BCN) foam was chosen as potential midsole materials because they have energy return and high strength to weight ratio properties. They also have high thermal stability, chemical stability and so forth, making BN and BCN foam useful for other applications like chemical control foam and memory foam. A one-step thermal chemical vapor deposition method using nickel (Ni) powder metallurgy template with melamine diborate as single solid precursor was used to synthesize the BCN. After which, the BCN was annealed to get BN. BN was synthesized, but it shrank after annealing. Secondary Electron Microscope (SEM) was used to observe the microstructures of BCN and BN. Images captured for BN did not have pores which makes it unlikely to have compressability for energy return to boost running performance. Using images captured for BCN foam for pore size analysis, pores of average diameter 0.643 um with a standard deviation of 0.332 was determined. Energy-Dispersive X-ray (EDX) revealed a homogenous distribution of elements in the BCN foam. X-Ray Diffraction (XRD) and Fourier Transform Infrared Spectroscopy (FTIR) confirmed the composition of BCN foam, with presence of BCN, BN and Carbon (C). BCN foam was determined to be synthesized successfully and concluded to be a potential material for improving running performance as midsole material. However, the BCN foam needs to be made into specifications that fulfil testing standards to have more accurate comparison with current midsole materials.